A ceramic-based microwave sensor for both permittivity and permeability characterization of materials. (8th June 2020) - Lu, Xiao; Tan, Qiulin; Zhang, Tong; Kou, Hairong; Zhang, Lei; Su, Shujing; Xiong, Jijun
Abstract: In this study, a novel microwave microstrip sensor is proposed for the simultaneous characterization of a material's permittivity and permeability. The electric permittivity and magnetic permeability of the material under test have similar effects on the frequency and quality factor of the sensor. To solve this problem, the structural characteristics of the proposed sensor make the strongest electric and magnetic fields distributed in different areas of the sensor to avoid the mutual effect of permittivity and permeability measurement. The proposed sensor is implemented using microstrip technology in which ring openings are located on either side of the microstrip line. The sensor is simulated and designed using a high- frequency structure simulator, and a numerical model of the sensor is established to extract the electric permittivity and magnetic permeability of the sample. The sensor is fabricated on high temperature co-fired ceramics (HTCC) substrates by screen printing techniques and it has the advantages of small size, excellent stability and adaptation to severe environments due to the HTCC substrates with high permittivity. In the S-band (2–4 GHz), samples of wood, PET, Fe3 O4 -PDMS are tested, and the relative electric permittivity and magnetic permeability of the samples obtained were consistent with the values available in the literature.